Giant mature teratoma in young female with right-sided hydronephrosis as a secondary complication: A case report - Sharma, Bharat Bhushan; Singh, Tanu; Mishra, Dhiraj Kumar; Sharma, Rohit; Nargotra, Natasha; Chugh, Nalin (Indian Journal of Case Reports, 2020)
Teratomas are the tumors made of different tissues. The composition includes hair, muscle, teeth, or bone. These tumors usually arise from ovary, testicle, or tailbone. These are asymptomatic when small in size without any complications, but become symptomatic when large and associated with secondary complications due to compression and displacement. We present the case of a 30-year-old female who had abdominal swelling of 2 months duration that increased in size rapidly. She was found to be having a big abdominopelvic mass in ultrasound, computerized tomography, and magnetic resonance imaging. There was moderate hydronephrosis on the right side which was due to the compression by this mass. She underwent total excision of the mass and it was turned out to be mature cystic teratoma. Cross-sectional modalities are quite sensitive in diagnosing the abdominal masses, especially teratomas. The diagnostic modalities further highlight the secondary features of the complications due to these masses.